2019
DOI: 10.1093/ofid/ofz013
|View full text |Cite
|
Sign up to set email alerts
|

Epidemic Clostridioides difficile Ribotype 027 Lineages: Comparisons of Texas Versus Worldwide Strains

Abstract: BackgroundThe epidemic Clostridioides difficile ribotype 027 strain resulted from the dissemination of 2 separate fluoroquinolone-resistant lineages: FQR1 and FQR2. Both lineages were reported to originate in North America; however, confirmatory large-scale investigations of C difficile ribotype 027 epidemiology using whole genome sequencing has not been undertaken in the United States.MethodsWhole genome sequencing and single-nucleotide polymorphism (SNP) analysis was performed on 76 clinical ribotype 027 iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 27 publications
0
10
2
Order By: Relevance
“…A convenience sample of 16 isolates from five distinct ribotypes underwent DNA extraction using either the QIAamp DNA minikit (Qiagen, Venlo, The Netherlands) or AnaPrep automated DNA extractor (BioChain Institute Inc., Newark, CA) as previously described ( 22 ). DNA was quantified by NanoDrop (Thermo Fisher Scientific, Waltham, MA) and Qubit (Thermo Fisher Scientific, Waltham, MA), and DNA quality was assessed using a BioAnalyzer (Agilent Technologies Inc., Santa Clara, CA).…”
Section: Methodsmentioning
confidence: 99%
“…A convenience sample of 16 isolates from five distinct ribotypes underwent DNA extraction using either the QIAamp DNA minikit (Qiagen, Venlo, The Netherlands) or AnaPrep automated DNA extractor (BioChain Institute Inc., Newark, CA) as previously described ( 22 ). DNA was quantified by NanoDrop (Thermo Fisher Scientific, Waltham, MA) and Qubit (Thermo Fisher Scientific, Waltham, MA), and DNA quality was assessed using a BioAnalyzer (Agilent Technologies Inc., Santa Clara, CA).…”
Section: Methodsmentioning
confidence: 99%
“…Most introductions corresponded to isolates from the FQR2 lineage, which has been recognized as the most widely distributed in the world [ 10 ]. However, newer studies report that the prevalence of the FQR1 and FQR2 lineages is similar in North America [ 56 ]. The most recent common ancestor analysis performed showed that the B1/NAP1/RT027/ST01 strain arrived in LA between 1998 and 2005 from North America (FQR1 and FQR2), Western Europe (FQR1 and FQR2) and Northern Europe (FQR2), confirming the rapid global dissemination of the FQR lineages after their emergence [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…A convenience sample of isolates from six distinct ribotypes underwent DNA extraction using either the QIAamp DNA Mini Kit (QIAGEN, Venlo, the Netherlands) or the AnaPrep automated DNA extractor (BioChain Institute Inc., Newark, CA, USA) as previously described. 17 DNA was quantified by NanoDrop (Thermo Fisher Scientific, Waltham, MA, USA) and Qubit (Thermo Fisher Scientific, Waltham, MA, USA) and DNA quality was assessed using a BioAnalyzer (Agilent Technologies Inc., Santa Clara, CA, USA). DNA libraries were prepared according to Illumina’s protocols, multiplexed on a flow cell and run on a NextSeq (Illumina Inc., San Diego, CA, USA) using paired-end sequencing.…”
Section: Methodsmentioning
confidence: 99%